POST‐IPO OPERATING PERFORMANCE IN BANGLADESH - Hossain, Md. Sajib; Khan, Muhammad Saifuddin (International Journal of Accounting & Finance Review, 2021)
This study attempts to investigate the change in the operating performance of firms as they go from private to public ownership. Using the data of all the non-financial firms, which floated initial public offerings (IPOs) from 2008 to 2015, this study finds that there is a significant decline in operating performance as measured by ROA, asset turnover, ROS, and OCFTA after the IPO and the decline continues for next two to three years with the highest deterioration of operating performance being observed in the immediate next year of IPO. Moreover, when the study uses age, debt ratio, sales, capital expenditure, and IPO event to explain the variation of the operating performance of IPO firms over time, it finds that IPO event negatively affects all measures of operating performance. Finally, the study finds that deterioration of the post-IPO operating performance is more pronounced for firms offering their securities with premium than firms offering securities without premium. JEL Classification Codes: G11, G12, G32.